How to suppress women's writing - Russ, Joanna, 1937-2011 (Louann Atkins Temple women & culture series, 2018)
"Are women able to achieve anything they set their minds to? In How to Suppress Women's Writing, award-winning novelist and scholar Joanna Russ lays bare the subtle--and not so subtle--strategies that society uses to ignore, condemn, or belittle women who produce literature. As relevant today as when it was first published in 1983, this book has motivated generations of readers with its powerful feminist critique."--Publisher's description.